Brittle stars (Echinodermata: Ophiuroidea) from the continental shelf off Angola and Namibia - Glück, Franziska U.; Stöhr, Sabine; Bochert, Ralf; Zettler, Michael L. (Zootaxa, 2012)
The fauna occurring in waters off South-West Africa is of a remarkable composition and highly diverse due to local waterbodies, flow conditions and abiotic factors. These parameters predominate as a result of the cooperation of a major coastalupwelling system (the Benguela Current Large Marine Ecosystem), the Benguela Current flowing northwards, thesouthward directed Angola Current and the Angola–Benguela Frontal Zone formed in the transition zone of both watercurrents. This area has been insufficiently explored within the last decades and major gaps in biodiversity knowledge existto date. Two expeditions were conducted in 2004/2008, which collected benthic fauna samples. This is a list of brittle starsfound and a comprehensive research study relating to Ophiuroidea in waters off Angola and Namibia. 17 species could beidentified at depths from the littoral zone down to 125 m. The known depth and geographical distributions were extended for several species. Short diagnoses and ecological data are included.